2015
DOI: 10.18488/journal.33/2015.2.4/33.4.35.43
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological Quality of Three Freshwater Fish Species from Two Local Markets in Region 6, (Corentyne, East Berbice) Guyana

Abstract: Present case study was carried out during 2013, to assess the microbiological quality of three freshwater fishes (Hoplosternum littorale, Cichlasoma bimaculatum and Hoplias malabaricus) offered for sale at two local markets in region 6. Fishes were examined for microbial quality and compared to the recommended levels of U.S Food and Drug Association (FDA) and Environmental Protection Agency (EPA) for fish and fisheries product. The results revealed based on the statistical test CHI-SQAURE that the microbial le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Even though it is often believed that freshly caught fish are devoid of bacteria, studies have shown that a variety of fish species contain a variety of bacteria that, in some circumstances, have the potential to be pathogenic, including staphylococcus and pseudomonas angulluseptica (Giddings et al, 2015).…”
Section: Microbiological Properties Of Fish Filletsmentioning
confidence: 99%
“…Even though it is often believed that freshly caught fish are devoid of bacteria, studies have shown that a variety of fish species contain a variety of bacteria that, in some circumstances, have the potential to be pathogenic, including staphylococcus and pseudomonas angulluseptica (Giddings et al, 2015).…”
Section: Microbiological Properties Of Fish Filletsmentioning
confidence: 99%